.(The effect of drying temperature and treatment of areca fruit(Areca cathecu L.)on the quantity of Whole Seed) - Susanto, Eko; -, Syahril; Waspodo, Priyo (Balai Besar Industri Agro, 1995)
Areca nut (Areca cathecu)is an export commodity which still face problem in its preparation.sun drying of areca nut done by the farmers needed 30 days or more.To reduce the drying time ,variation of drying temperature and treatment on the fruit was studied.The study aimed at obtaining the proper drying condition after which the dried fruit could be easly broken and the percantageÂ of whole nut is high.The temperature used were 60,80,and 100 degree C,while the treatment applied were whole fruit (no treatment),scratched fruit and partially peeled fruit.The result showed that the best drying temperature was 100 degree C.The drying time needed was hours which resulted in 80%whole nut with 13.66% moisture content.